[Intro] Standards and Their Containers: Introduction to the Thematic Issue on Histories of Microbial Pathogens from the Colonial to the Postcolonial Eras - Aro Velmet; Claas Kirchhelle (Engaging Science, Technology, and Society)
Standards and infrastructures have become ubiquitous objects of study in STS. They are critical to the global work of microbiology. However, the role of early twentieth-century colonial, military, and capitalist expansion in the production of these infrastructures is underappreciated. Further, the role of microbial “resistance” in shaping and changing the global microbiological order needs better elucidation. This requires connecting the technical work done in laboratories across the world with the global processes that have shaped much of the twentieth century. The articles in this thematic collection cast light on neglected temporal and geographic areas of human-microbial interactions, explore new ways of (re)reading historical sources to reveal (post)colonial distortions of scientific practice and acts of resistance, and underline the need to trace microbes and associated biomedical interventions not only within laboratories, but also within wider human and non-human environments.